Pengembangan Model Pembelajaran Mandiri Untuk Meningkatkan Kemampuan Berfikir Kritis Mahasiswa Sastra Jepang - Oslan Amril; Diana Kartika; Tienn Immerry; Ulfaizah Ulfaizah; Jelita Maharani Jelita Maharani; Susi Widianti; Titik Fujita Yusandara (Pedagogi: Jurnal Ilmu Pendidikan, 2023)
This research was conducted based on the low level of students' critical thinking skills because the learning process carried out in class was considered less effective in developing students' interests, talents and potential. The purpose of this research is generally carried out to determine the extent to which the application of the independent learning method in improving student learning outcomes of the Japanese Literature Study Program. Specifically, this research aims to describe the steps for implementing the self-learning method which includes planning, implementation, and evaluation, as well as describing the application of the self-learning method. Independent learning methods are implemented to overcome these problems so that students have motivation, more learning experiences, and students will be more independent. The data collection techniques used were questionnaires, interviews, and data validation as a review to see the validity of the data. The results of the study obtained data. Learning activities with a critical thinking approach had an impact on changing the way students think. These changes can be seen from the questionnaire data which shows that the majority of the sample agreed with statement number 8 as much as 76%. In the next sequence is statement no.15 with the number of those who answered agree as much as 75%. Statements no.12, no.13, and no.16 received 60% answers. Meanwhile statement.